Are Trace Elements Provided for Children on Long-Term Parenteral Nutrition Adequate to Meet Their Needs? - Hanna Romanowska; Mikołaj Danko; Anna Borkowska; Katarzyna Popińska; Marta Sibilska; Joanna Żydak; Joanna Wielopolska; Klaudia Bartoszewicz; Agnieszka Szlagatys-Sidorkiewicz; Janusz Książyk (Life)
Background: We conducted a cross-sectional study to investigate whether children receiving long-term parenteral nutrition (LPN) are at risk of imbalances in selected trace elements. Methods: Serum levels of manganese, zinc, copper, selenium, and iodine were measured in 83 children on LPN and compared with 121 healthy controls. Children with signs of infection or elevated C-reactive protein levels were excluded. Elemental analysis was performed using inductively coupled plasma mass spectrometry (ICP-MS). Results: Manganese and copper levels were significantly lower in the study group compared with controls (p < 0.001) but remained within normal ranges. Iodine levels were also significantly lower in the study group (p < 0.05), though pediatric reference values are lacking. Zinc and selenium levels were significantly higher in the study group (p < 0.001), with median levels within normal ranges in both groups. Zinc, selenium, and iodine levels were higher in patients weighing ≤15 kg (p < 0.001, p < 0.001, p < 0.02). Conclusions: Serum concentrations of manganese, copper, and selenium in the study group remained within normal ranges, even though children weighing over 15 kg received doses below those recommended by scientific guidelines. An iodine intake below 1 μg/kg/day in patients weighing over 15 kg appears insufficient. Patients on LPN required a higher zinc intake than current recommendations.